Sexual Dimorphism and Aging in the Human Hyppocampus: Identification, Validation, and Impact of Differentially Expressed Genes by Factorial Microarray and Network Analysis - Guebel, Daniel V.; Torres, Néstor V. (Frontiers in Aging Neuroscience, 2016)
Motivation: In the brain of elderly-healthy individuals, the effects of sexual dimorphism and those due to normal ageing appear overlapped. Discrimination of these two dimensions would powerfully contribute to a better understanding of the aetiology of some neurodegenerative diseases, such as “sporadic” Alzheimer. Methods: Following a system biology approach, top-down and bottom-up strategies were combined. First, public transcriptome data corresponding to the transition from adulthood to the ageing stage in normal, human hippocampus were analysed through an optimized microarray post-processing (Q-GDEMAR method) together with a proper experimental design (full factorial analysis). Second, the identified genes were placed in context by building compatible networks. The subsequent ontology analyses carried out on these networks clarify the main functionalities involved. Results: Noticeably we could identify large sets of genes according to three groups: those that exclusively depend on the sex, those that exclusively depend on the age, and those that depend on the particular combinations of sex and age (interaction). The genes identified were validated against three independent sources (a proteomic study of ageing, a senescence database, and a mitochondrial genetic database). We arrived to several new inferences about the biological functions compromised during ageing in two ways: by taking into account the sex-independent effects of ageing, and considering the interaction between age and sex where pertinent. In particular, we discuss the impact of our findings on the functions of mitochondria, autophagy, mitophagia, and microRNAs. Conclusions: The evidence obtained herein supports the occurrence of significant neurobiological differences in the hippocampus, not only between adult and elderly individuals, but between old-healthy women and old-healthy men. Hence, to obtain realistic results in further analysis of the transition from the normal ageing to incipient Alzheimer, the features derived from the sexual dimorphism in hippocampus should be explicitly considered.